Pengaruh Literasi Pajak, Persepsi Kondisi Keuangan, Dan Kesadaran Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Kota Surabaya - Hanifah Dewi Argyanti; Lilik Mardiana (Jurnal Ekonomi dan Bisnis Digital, 2024)
This Study aims to analyse the effect of tax literacy, perceived financial condition, and taxpayer awareness on MSME taxpayer compliance in Surabaya City, both partially and simultaneously. The sample of this research is MSME owners who market their products on the Peken Surabaya website. This research uses quantitative methods. The data collection method uses purposive sampling using a questionnaire. This study uses multiple linear regression analysis methods to determine the extent to wich tax literacy, perceived financial condition, and taxpayer awareness affect the level of taxpayer compliance. The results of study indicate that tax literacy, perceived financial condition, and taxpayer awareness have a positive and significant effect on MSME taxpayer compliance. In addition, this study found that 26.1% of variability in taxpayer compliance is influenced by other variables not examined in this study.